2013
DOI: 10.1007/s12020-013-9902-5
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial fat thickness and left ventricular mass in subjects with adrenal incidentaloma

Abstract: Emerging evidences indicate that patients diagnosed with adrenal incidentaloma may present with cardiovascular complications. Epicardial fat is known to play a role in left ventricle (LV) changes. Whether epicardial fat can be associated with LV mass (LVM) in patients with incidentaloma is unknown. We test the hypothesis that echocardiographic epicardial fat thickness is independently related to LVM in a well-studied group of subjects with adrenal incidentaloma. 46 consecutive patients (age 59 ± 9 years) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 15 publications
4
31
0
Order By: Relevance
“…Our finding of a correlation between adrenal gland volume, hypercortisolism and increased PAT may point to the role of HPAA activation promoting cardiovascular risks in depression. Interestingly, a recent study in patients with adrenal incidentalomas also found an association between adrenal gland volume with increased epicardial fat (Iacobellis et al, 2013). Incidentalomas are adrenal masses that are increasingly recognized with the widespread use of thoracic and abdominal imaging, and it has recently suggested that patients with adrenal incidentalomas may have an increased cardiovascular risk (Giordano et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding of a correlation between adrenal gland volume, hypercortisolism and increased PAT may point to the role of HPAA activation promoting cardiovascular risks in depression. Interestingly, a recent study in patients with adrenal incidentalomas also found an association between adrenal gland volume with increased epicardial fat (Iacobellis et al, 2013). Incidentalomas are adrenal masses that are increasingly recognized with the widespread use of thoracic and abdominal imaging, and it has recently suggested that patients with adrenal incidentalomas may have an increased cardiovascular risk (Giordano et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with adrenal incidentalomas, accumulation of IAT and epicardial adipose tissue has recently been reported (Debono et al, 2013;Iacobellis et al, 2013). Therefore we examined IAT, PAT and adrenal gland volume and aimed at testing the following hypotheses:…”
Section: Introductionmentioning
confidence: 99%
“…Patients with adrenal adenomas and sCS have been found to have increased LV mass compared to healthy controls and subjects harbouring non-functioning adrenal adenomas (191). Significant structural and functional modifications of the heart and vasculature can also be detected in paediatric CS patients (192).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…We demonstrated here that an increase in EFV is significantly related to LV remodeling. Indeed, the relationship between epicardial fat and LV mass had been established previously in studies carried out in different populations [5][6][7][8], but our study is the first in population of obese patients with severe obstructive sleep apnea treated by a continuous positive airway pressure. Our data are consistent with previous studies supporting a negative role of epicardial fat deposit International Journal of Cardiology 179 (2015) 218-219 on cardiac function rather than a global effect of body volume obesity [9].…”
Section: To the Editormentioning
confidence: 67%